A risk assessment of Europe's black truffle sector under predicted climate change - Thomas, Paul; Büntgen, Ulf (The Science of the total environment, 2019)
The black truffle (Tuber melanosporum) is a highly revered culinary icon species that grows symbiotically with its host trees across several parts of southern Europe. Where harvested under natural or cultivated conditions, truffles can have a significant socioeconomic impact and may even form a key component of cultural identity. Although some aspects of truffle biology and ecology have been elucidated recently, the role of abiotic, environmental and climatic factors in the production and maturation of their fruitbodies is still largely unknown. Based on 36-year-long, continuous records of Mediterranean truffle yield, we demonstrate that decreased summer precipitation together with increased summer temperatures significantly reduce the fungus' subsequent winter harvest. Using state-of-the-art climate model projections, we predict that a significant decline of 78-100% in southern European truffle production is likely to occur between 2071 and 2100. The additional threats of forecasted heatwaves, forest fires, pest and disease outbreaks are discussed along with socioeconomic and ecological consequences of a warmer and dryer future climate. Our results emphasize the need for unravelling the direct and indirect effects of climate change on Europe's truffle sector and underline the importance of conservation initiatives at local to international scales.
Keywords: Agriculture; Fungal ecology; hodnocení rizik; Climate Change; France; Risk Assessment; Climate change; Spain; Tuber melanosporum; Agaricales; Ectomycorrhiza fungi; Francie; Itálie; Truffle yield; zemědělství; Španělsko; klimatické změny; Ascomycota; Italy; Périgord truffle